Relationship between summer gains of yearling steers on bluestem pastures and feeder grade, shade of color, weight at the start of the grazing season, and previous winter gain. - Holland, L.A.; Wheat, J.D.; Smith, E.F.; Smith, W.H.; Good, D.L.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
The Department of Animal Husbandry purchases steer calves each fall to be wintered and grazed the following summer in studies of different methods of managing bluestem pastures. This affords opportunities to study the relationships between summer gains and feeder grade, shade of color, weight at the start of the grazing season, and previous winter gain. Several years will elapse before definite conclusions can be drawn concerning these relationships. Following, however, is a report of progress to date of the studies made of these factors.
Keywords: Beef; Gain; Bluestem pasture; Color